2002
DOI: 10.1038/sj.onc.1205609
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and chromatin – unraveling the tangled web

Abstract: Methylation of cytosines within the CpG dinucleotide by DNA methyltransferases is involved in regulating transcription and chromatin structure, controlling the spread of parasitic elements, maintaining genome stability in the face of vast amounts of repetitive DNA, and X chromosome inactivation. Cellular DNA methylation is highly compartmentalized over the mammalian genome and this compartmentalization is essential for embryonic development. When the complicated mechanisms that control which DNA sequences beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
310
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(317 citation statements)
references
References 134 publications
(186 reference statements)
1
310
0
6
Order By: Relevance
“…DNMT1 is generally considered to be a maintenance methylase, although it also has de novo methylase activity (Bestor, 2000;Robertson, 2002). Both DNMT3A and DNMT3B catalyse de novo methylation of DNA sequences (Li, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 is generally considered to be a maintenance methylase, although it also has de novo methylase activity (Bestor, 2000;Robertson, 2002). Both DNMT3A and DNMT3B catalyse de novo methylation of DNA sequences (Li, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chromatin at inactive promoters is generally hypoacetylated by histone deacetylases (HDAC) that can be inhibited by HDAC inhibitors such as Trichostatin A (TSA). Because DNMT1 has been found to interact physically with HDACs, DNA-methylation and histone deacetylation may function through a common mechanistic pathway to repress transcription (Rountree et al, 2000;Dobosy and Selker, 2001;Robertson, 2002). The use of both TSA and AZA has synergistic effects in activating epigenetically silenced genes (Cameron et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is documented that the methylation of CpG islands is associated with changes in chromatin structure and the repression of gene transcription (Robertson, 2002). Many studies have also revealed that aberrant DNA methylation in tumor suppressor genes such as p16/INK4a, p19/ARF and p21/WAF1 are early events in the process of tumorigenesis (Robertson, 2001).…”
Section: Introductionmentioning
confidence: 99%